DYRK1A, a Dosage-Sensitive Gene Involved in Neurodevelopmental Disorders, Is a Target for Drug Development in Down Syndrome - Duchon, Arnaud; Herault, Yann (Frontiers in Behavioral Neuroscience, 2016)
Down syndrome (DS) is one of the leading causes of intellectual disability, and patients with DS face various health issues, including learning and memory deficits, congenital heart disease, Alzheimer’s disease (AD), leukemia and cancer, leading to huge medical and social costs. Remarkable advances on DS research have been made in improving cognitive function in mouse models for future therapeutic approaches in patients. Among the different approaches, DYRK1A inhibitors have emerged as promising therapeutics to reduce DS cognitive deficits. DYRK1A is a dual-specificity kinase that is overexpressed in DS and plays a key role in neurogenesis, outgrowth of axons and dendrites, neuronal trafficking and aging. Its pivotal role in the DS phenotype makes it a prime target for the development of therapeutics. Recently, disruption of DYRK1A has been found in Autosomal Dominant Mental Retardation 7 (MRD7), resulting in severe mental deficiency. Recent advances in the development of kinase inhibitors are expected, in the near future, to remove DS from the list of incurable diseases, providing certain conditions such as drug dosage and correct timing for the optimum long-term treatment. In addition the exact molecular and cellular mechanisms that are targeted by the inhibition of DYRK1A are still to be discovered.